A case of iatrogenic CNV following macular surgery - Akshay Prashant Agnihotri; Ines D. Nagel; Anna Heinke; Zachary A. Koretz; William R. Freeman (American Journal of Ophthalmology Case Reports)
Purpose: To report a case of iatrogenic trauma related choroidal neovascularization (CNV) Methods: A 66 year old female presented with complaints of distortion of vision in the right eye. A diagnosis of epiretinal membrane (ERM) foveoschisis was made and the patient was recommended surgery. During surgery an inadvertent touch of the retina occurred. Post operatively, an iatrogenic choroidal neovascular membrane was diagnosed. Results: Post-operative optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) revealed a CNV which was treated with intravitreal Bevacizumab. The visual acuity improved remarkably. The intraretinal and subretinal fluid resolved and the macula was almost completely dry at final visit. Conclusion: ERM surgery is one of the common procedures in vitreoretinal surgery. Iatrogenic CNV is a reported but rare complication following inadvertent trauma during surgery. We report a successful outcome of iatrogenic CNV treated with intravitreal injections of Bevacizumab.